Združitev odzivov na podnebne spremembe in tematskih področij starosti prijaznih mest - Bayar, Rümeysa (Urbani izziv, 2023)
This study focuses on older adults, who are disproportionately vulnerable to climate change due to their health, physical, and socioeconomic conditions. On the one hand, climate change has grown into the most challenging issue on the international agenda for the twenty-first century due to its adverse impacts. On the other hand, the global population has been ageing rapidly, especially in urban areas. The link between these two major concerns is unclear in theory and practice; hence, easy-touse universal guidelines offering possible solutions for governments, institutions, and communities for irremediable impacts are an urgent necessity. Based on this imperative, this article presents climate change–responsive age-friendly city domains through a critical literature review. Seven domains are prioritized at various scales to represent the core planning areas of age-friendliness and climate-change resilience in urban areas: environmental safety, information and participation, health and social services on the city scale, surroundings and transportation on the neighbourhood scale, outdoor spaces and thermal comfort, and housing on the housing cluster scale. The interaction between these two concerns in the framework provided by this study contributes to raising awareness, building actions, and directing policies from a global perspective.
Keywords: age-friendly city; climate change; podnebne spremembe; population ageing; staranje prebivalstva; starosti prijazno mesto; sustainability; trajnostni razvoj; urban policy; urbanistična politika